Improvement of event accessibility and integration measuresfor people with special needs - Variakojienė, Jolita; Gasperavičiūtė, Gabija (Turystyka i Rozwój Regionalny, 2025)
This study investigates the accessibility barriers encountered by individuals withdisabilities in participating in public events in Lithuania and explores integration measuresaimed at improving inclusion. Drawing on comparative quantitative research conducted in2021 and 2024 (N = 253 in 2024), the findings indicate a positive shift in perceptions of eventaccessibility, with the average rating increasing from 5.85 to 7.22. Despite these improvements,significant challenges persist, including physical, financial, and informational barriersthat hinder full participation. The research highlights successful international practices, suchas those implemented at EXPO 2020 Dubai and MCM London Comic Con, which encompassphysical adaptations, sensory tools, accessible information, and emotional support measures.The study underscores the need for a holistic, multi-dimensional approach to accessibility thataddresses both structural barriers and societal attitudes, thereby promoting greater inclusionand social integration of individuals with disabilities in public life.